Isolasi dan Identifikasi Bakteri serta Jamur pada Bekasam Ikan Mujair dengan Perlakuan Ekstrak Kunyit sebagai Agen Antimikroba - Dini Anjani; Ardi Mustakim (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to isolate and identify microorganisms in the form of bacteria and fungi in tilapia fish waste and to demonstrate the effectiveness of turmeric extract (Curcuma longa Linn.) as an antimicrobial agent. Tilapia fish waste samples were fermented for seven days and then microorganisms were isolated using Nutrient Agar (NA) media for bacteria and Potato Dextrose Agar (PDA) for fungi. Turmeric extract treatment was carried out using the disc diffusion method. The results showed the presence of several species of Gram-positive and Gram-negative bacteria, as well as fungal colonies with dominant characteristics of Aspergillus sp. and Fusarium sp. Turmeric extract with a concentration of 20% showed a significant inhibition zone against the growth of pathogenic bacteria and fungi. The content of secondary metabolites such as alkaloids, tannins, and phenolics in turmeric extract is thought to be the main factor in antimicrobial activity.